Small Town Government with Big World Challenges - Peacock, Valerie (Maine Policy Review, 2023)
Bar Harbor's relationship with tourism is shifting from a focus on attracting visitors to the need to balance economic interests with the quality of life for residents. As a coastal community, cruise ship tourism is at the center of the debate about the appropriate scale of visitation. This article focuses on the challenges and recommendations for how a small town with a Town Meeting-Town Council form of government might manage cruise ship tourism over changing times.
Keywords: Bar Harbor; cruise ships; tourism management; municipal government